USE OF ANALYTICAL PROCEDURES TO IMPROVE THE QUALITY OF AUDIT OF FINANCIAL RESULTS - Tojiboeva Sh.A. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article discusses the use of analytical procedures in the audit of financial results in enterprises. The methods of factor analysis of financial results given in the study make it possible to correctly assess the financial and economic activities of enterprises, search for on-farm reserves to increase profits and thereby ensure their stable financial condition, and improve the quality of the audit.